Development of a Low-Cost Icebox for Preservation and Transportation of Iced Fish (Progressive Agriculture, 2013)
A low-cost icebox was developed and its efficacy in icing fish was evaluated in order to minimize huge post-harvest loss and ensure adequate price of wet fish through quality maintenance. Traditional bamboo basket capable of containing 25-30 kg fresh fish was wrapped inside, bottom and top twice by polythene gunny sacs. In between the two layers of gunny sacs, a layer of plant leave mat (hogla mat) and a layer of old nylon net/cloths were placed for insulation. A small plastic pipe (1 cm diameter, 60 cm long) was inserted through the bottom to drain out melted water. The rear end of the pipe was kept fasten with the rim of the basket. To keep the iced fish inside of the wrapped basket, a separate plain polythene sheet was used. Freshly caught Puntius sophore (5.8 ± 0.4 cm) and Cirrhinus mrigala (16.4 ± 1.3 cm) were preserved under adequate icing for 7 to 10 days. Temperature of the iced fish inside was maintained between 0.4o to 3.1oC. Freshness of the fish kept in the new icebox during preservation and transportation was investigated through sensory and biochemical methods. No chance of secondary contamination was found in new ice box because the fish could not come in contact of the basket materials. The device was very easy to clean and keep clean. Shape of filled icebox was found regular and stout with no sign of breakage and leakage. Rate of melting of ice was 23.0 ± 1.6% in 24 hours. Replacement of ice was done at such rate. Melted water was adequately drained out. Iced C. mrigala and P. sophore kept in the icebox were in excellent quality in terms of both sensory and biochemical indicators till the end of 7th or 10th day, respectively. The study suggested that the new icebox was effective in preserving and transporting iced fish.DOI: http://dx.doi.org/10.3329/pa.v19i2.16952 Progress. Agric. 19(2): 119 - 127, 2008